Pengembangan Modul Ajar Matematika Sesuai Kurikulum Merdeka Materi Pecahan Berbasis Pendekatan Matematika Realistik untuk Kelas V Sekolah Dasar - Barumbun, Mardyanto; Kusnadi, Dedi; Dwiyanti, Anik; Liani, Ahyani Mirah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aimed to develop a teaching module on fractions for 5th-grade elementary school students, designed using a realistic approach and tailored for implementation within the framework of the Merdeka Curriculum. The development research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which was evaluated through expert validation of media and content, as well as student interest response and teacher practicality response regarding the module. The validation results from both media and content experts indicated that the developed module was highly suitable, with percentage scores of 94% and 95%, respectively. Additionally, student responses to the learning experiences facilitated by teachers using the developed module were highly positive, ranging from interested to highly interested. Moreover, teacher responses regarding the practicality, effectiveness, efficiency, and creativity of the developed module obtained a percentage score of 98%, signifying excellent quality. These research findings demonstrate that the developed teaching module is both suitable and practical for use by teachers in teaching fractions to 5th-grade elementary school students, with the learning experiences facilitated by this module receiving positive responses from students.